2019
DOI: 10.15537/smj.2019.5.24153
|View full text |Cite
|
Sign up to set email alerts
|

Suicide attempts and related factors in schizophrenia patients

Abstract: Objectives: To investigate the relationship between suicide attempts and demographic-clinical variables and to assess the methods used in suicide attempts by comparing schizophrenia patients with and without suicide attempts. Methods: A retrospective study with a total of 223 schizophrenia patients aged 18-65 years that were admitted to the Department of Psychiatry, Selcuk University and the Beyhekim Psychiatric Clinic Konya Training and Research Hospital, Konya, Turkey… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(14 citation statements)
references
References 36 publications
2
7
0
5
Order By: Relevance
“…The existing studies have tried to identified several factors predicting the risk of suicide in individuals with SCZ, which include younger age, male gender, lack of social support, unemployment, being unmarried, being well-educated, being intelligent ( 21 ), a family history of psychiatric disorder, having poor work functioning, higher number of hospitalizations ( 25 ), presence of a previous suicide attempt, poor adherence to treatment, history of suicidal behavior ( 20 ), having had recent (i.e., within past 3 months) life events ( 26 ), having access to lethal means, and seriousness of psychiatric pathology ( 21 ), comorbid affective disorder and the strong stigma of mental illness in rural areas ( 16 ). Furthermore, some studies have also reported that a combination of genetic markers and early traumatic life events might indeed be used to identify patients at risk for suicide attempt in SCZ.…”
Section: Introductionmentioning
confidence: 99%
“…The existing studies have tried to identified several factors predicting the risk of suicide in individuals with SCZ, which include younger age, male gender, lack of social support, unemployment, being unmarried, being well-educated, being intelligent ( 21 ), a family history of psychiatric disorder, having poor work functioning, higher number of hospitalizations ( 25 ), presence of a previous suicide attempt, poor adherence to treatment, history of suicidal behavior ( 20 ), having had recent (i.e., within past 3 months) life events ( 26 ), having access to lethal means, and seriousness of psychiatric pathology ( 21 ), comorbid affective disorder and the strong stigma of mental illness in rural areas ( 16 ). Furthermore, some studies have also reported that a combination of genetic markers and early traumatic life events might indeed be used to identify patients at risk for suicide attempt in SCZ.…”
Section: Introductionmentioning
confidence: 99%
“…The evaluation of the risk factors and predicting the suicidal outcome in the schizophrenic 1 1 1 patient population is a tough task for the physician. However, knowing these possible risk factors helps the physician better evaluate and address patient beliefs and values related to the disorder [8][9][10][11].…”
Section: Discussionmentioning
confidence: 99%
“…There are several risk factors accountable for the suicidal behavior in this patient population [2][3][4][5][6]. The most common ones are white ethnicity, younger age, unmarried, higher intellectual level, social isolation, gradual onset of illness, hopelessness, co-morbid substance abuse, previous hospitalizations, previous suicide attempts, family history of suicide, family stress, impulsivity, positive symptoms of schizophrenia, unemployment, prolonged illness, the greater insight of the illness and others [7][8][9][10][11]. We conducted this review article to determine the significance of antipsychotic medication compliance in Schizophrenic patients to reduce suicidal ideation and hospitalizations.…”
Section: Introductionmentioning
confidence: 99%
“…20 Stopa suicidalnosti kod adolescenata nije dovoljno istražena, a u odrasloj populaciji je utvrđeno da je 40,8% bolesnika sa shizofrenijom pokušalo samoubojstvo barem jednom i da je 39,6% bolesnika sa shizofrenijom koji su pokušali samoubojstvo imalo ponavljajuće pokušaje samoubojstva. 21 Oni s pokušajima samoubojstva imali su znatno dulje prosječno trajanje neliječene psihoze i veći ukupni broj hospitalizacija, u odnosu na one bez pokušaja samoubojstva. 21 Prema nekim istraživanjima utvrđena je statistički značajna razlika u prisutnosti traumatičnih životnih događaja između osoba sa i bez pokušaja samoubojstva.…”
Section: Rezultatiunclassified